The impact of magnetism on tidal dynamics in the convective envelope of low-mass stars. Issue Volume 15:Issue S354(2019) (June 2019) - Astoul, A.; Mathis, S.; Baruteau, C.; Gallet, F.; Strugarek, A.; Augustson, K. C.; Brun, A. S.; Bolmont, E.
Abstract: For the shortest period exoplanets, star-planet tidal interactions are likely to have played a major role in the ultimate orbital evolution of the planets and on the spin evolution of the host stars. Although low-mass stars are magnetically active objects, the question of how the star's magnetic field impacts the excitation, propagation and dissipation of tidal waves remains open. We have derived the magnetic contribution to the tidal interaction and estimated its amplitude throughout the structural and rotational evolution of low-mass stars (from K to F-type). We find that the star's magnetic field has little influence on the excitation of tidal waves in nearly circular and coplanar Hot-Jupiter systems, but that it has a major impact on the way waves are dissipated.